PROVISION CAPACITY OF SERVICE DELIVERY FACILITIES FOR CHILDREN WITH HEARING LOSS IN HAI PHONG, VIETNAM - XUONG TUYET NGUYEN; HA NGOC NGUYEN; TRAM VAN TA; VU KIEN TRAN; HIEN THE PHAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Hearing loss is a commonly occurring disability that affects 466 million people worldwide. This study aimed at determining the actual situations of early intervention delivery facilities for children with hearing loss. Out of this affected population, 7% are children (34 million) who, along with their families, grapple with the serious lifelong problems that accompany the disease. Methods: This descriptive cross-sectional study was conducted with facilities investigated consisting of a school for the deaf, hospitals, an audiology center, and a social agency in Hai Phong province from January 2013 to December 2014. A sample composed of 353 children was also recruited. Results: The examined facilities suffer from shortcomings in provision capacity, which manifest in deficient materials, supplies and equipment, and human resources; the lack of interdisciplinary coordination of activities; inadequate community awareness; and the unaddressed need for early detection and intervention. The conditions of most of the children (98%) were detected by their families, and among those who were clinically diagnosed, the majority (76.8%) received such diagnosis at central hospitals. Hearing impairment among the children were detected, diagnosed, and subjected to intervention at a very late stage (on average, at ages 22.3, 34, and 32.5 months, respectively), thereby compelling up to 63.6% of the families to struggle with their children’s hearing loss. Conclusion: Solutions to current interventions are needed to enhance service delivery systems and guarantee early detection as well as timely and appropriate treatment.